Management of Santri Character Education in Answering the Challenges of Modernity in the Era of Globalization - Nur Mahmudah, Fitri; Samino, Samino (Journal of Law and Social Politics, 2024)
Background: Islamic boarding schools (pesantren) are increasingly required to adapt to the rapid advancement of science, technology, and globalization. As an unavoidable global dynamic, globalization has brought significant changes to various aspects of life, including education. Consequently, pesantren are encouraged to respond proactively by integrating traditional Islamic values with modern knowledge and technological developments while maintaining their distinctive educational identity. Objective: This study aims to analyze the management of santri character education in Islamic boarding schools in responding to the challenges of modernity in the era of globalization. Methods: The study employs a qualitative approach with a descriptive-analytical design. Data were collected through observations, interviews, and documentation to examine leadership patterns, teaching strategies, communication systems, and decision-making processes within pesantren institutions. Results: The findings indicate that Islamic boarding schools have undergone positive structural and cultural transformations. These changes include more open leadership patterns, improved relationships between leaders and santri, more effective communication, and participatory decision-making processes. Pesantren have revitalized teaching methods to foster scientific traditions and lifelong learning, strengthened leadership adaptability, and developed more conducive, comprehensive, and empowering learning environments. Conclusion: The management of santri character education in Islamic boarding schools has demonstrated a constructive response to the challenges of modernity. Through adaptive leadership, revitalized teaching practices, and an inclusive learning environment, pesantren are able to preserve Islamic values while effectively engaging with the demands of globalization.